Lost ebook - Patterson, James (Tom Moon, 2020)
In this action-packed thriller, Miami just got a lot more dangerous—especially for one innocent young woman running for her life.  The city of Miami is Detective Tom Moon's back yard. He's always kept it local, attending University of Miami on a football scholarship, and, as a Miami PD officer, protecting the city's most vulnerable. Now, as the new leader of an FBI task force called "Operation Guardian," it's his mission to combat international crime. Moon's investigative team discovers that the opportunistic "Blood Brothers"—Russian nationals Roman and Emile Rostoff—have evaded authorities while building a vast, powerful, and deadly crime syndicate throughout Europe and metropolitan Miami. Moon played offense for U of M, but he's on the other side of the field this time. And as the Rostoffs zero in on a target dear to Tom, they're not playing by anyone's rules.